Description of two new species of Tonsilla Wang & Yin, 1992 with an updated key to species (Araneae, Agelenidae) - Liu, Ke-ke (Zookeys, 2020)
Two new species of Tonsilla Wang & Yin, 1992 are described from Jinggang Mountain National Nature Reserve, Jiangxi Province, China: T.jinggangensis K. Liu & X. Xu, sp. nov. (♀) and T.subyanlingensis K. Liu & X. Xu, sp. nov. (♂♀). The new species are illustrated, and their distributions are mapped. Detailed generic characters and an updated key to Tonsilla species are also given.